Surgery of the head and neck in patient with Kniest dysplasia: Is wound healing an issue?. (February 2017) - Husain, Qasim; Cho, Jungsuk; Neugarten, Jay; Modi, Vikash K.
Abstract: Kniest dysplasia is a type II collagen disorder that arises from a genetic mutation of the COL2A1 gene that results in short stature, midface anomalies, tracheomalacia, and hearing loss. Disruption of the normal collagen pathway can lead to many changes given its critical role in the body, and can cause complications with respect to wound healing. We present a case in which a patient with Kniest dysplasia successfully underwent multiple procedures in the head and neck region including cochlear implantation, mandibular distraction, palatoplasty, and laryngotracheal reconstruction. All procedures did not have any associated complications with respect to wound healing, indicating that surgery in this population can take place as indicated and surgery should not be contraindicated or delayed.